PV cell activation selectively affects different decision-making components. - Lilia Kukovska (22683586) (2025)
A) Response latency for time to first lick in laser off (0 mW/mm2) vs. laser on (0.04–0.43 mW/mm2) in the early window condition (easy discrimination) for ‘go’ (left panel) and ‘no-go’ (right panel) stimuli. Circle, median; line, 95% CI of bootstrapping. Asterisks indicate significant deviation (p < 0.05) from no laser stimulation control condition. B) Normalized decision criterion c across time windows in easy (left panel) and difficult (right panel) discriminations. Shaded line is the 95% CI of data shuffled 1,000 times, using bootstrapping with replacement. Horizontal bars with corresponding colors indicate significant deviation (p < 0.05) from no laser stimulation. Data is normalized by subtracting the value of the 0 power level (see Methods). C) Licking proportion in response to the presentation of the ‘go’ (solid line) and ‘no-go’ (dashed line) stimuli. Plots in C–E) show data for the entire window condition (easy discrimination), with colors ranging from blue to red corresponding to increasing laser powers, ranging from 0.04 to 0.43 mW/mm2, as indicated in A). D) Time course of classification accuracy of running speed (left panel) and pupil size (right panel) linear decoders (probability of correctly identifying ‘go’ vs. ‘no-go’ trials), based on the cumulative evidence of running speed or pupil diameter for different PV cell activation levels. E) Normal cumulative distribution function (solid line) with fixed mean and standard deviation as a model fit for cumulative d’ (circles) across stimulus presentation (for visualization purposes, every second data point is shown). The number of mice and sessions is the same as in Figs 2 and 3.